The prefabrication in domestic architecture after the Second World War. The case of levittowns in USA - Guerrero González, Beatriz (Centro Universitario de Arte, Arquitectura y Diseño, 2019)
To look back at a fundamental fact of the history of housing construction, as it was prefabrication in the United States in the immediate years after the Second World War, allows us to analyze the phenomenon from various points of view: professional, technical, economic, political, but where the most important should always be the social. The prefabrication was used only as a means to try to remedy a situation of housing need at a certain time, lowering costs and offering construction speed and not as the real solution to all the problems faced by the American society in those moments Therefore, what can we learn from this experience in our current situation and in the face of the imminent fourth Industrial Revolution?